Dakwah Di Tengah Pluralitas Masyarakat - Muhammad Qorib (Intiqad: Jurnal Agama dan Pendidikan Islam, 2018)
Da'wah is not only a matter of the afterlife, but also world affairs to create an Islamic social system. In the context of Indonesia, da'wah can be understood as a very strategic medium for the reconstruction of a pluralistic community culture. It is at this level that da'wah should play itself, namely as a force which can manage plurality into energy that can awaken the nation's civilization. Therefore, a paradigm and perspective is needed in addressing this highly pluralistic society. Da'wah must be a binding factor within the society, not a breaking factor which can strengthen the differences. Plurality is an interesting fact to be responded wisely. Plurality will greatly provide valuable lessons and wisdom in carrying out da'wah. Allah creates a plurality to enrich people so that they can complement and learn each other.